Absent mindfulness: mediation analyses of the relationship between adverse childhood experiences and disordered eating among young adults - Royer, Michael F.; Cosgrove, Kelly; Wharton, Christopher (Frontiers in Child and Adolescent Psychiatry, 2023)
Recent evidence has indicated that adverse childhood experiences (ACEs) involving abuse, neglect, and other potentially traumatic occurrences are predictive of disordered eating among young adults. Previous findings have suggested that ACEs and disordered eating were both inversely related to mindfulness. No known studies have examined the extent to which mindfulness mediates the link between ACEs and disordered eating. This study was conducted among a sample of 144 young adults in the U.S. between the ages of 18 and 26 years. Primary study variables included ACEs, mindfulness, and disordered eating. Univariate and multivariable regression analyses assessed the link between ACEs and disordered eating. Mediation analyses examined whether mindfulness mediated the link between ACEs and disordered eating. Multivariable analyses statistically adjusted for the covariates of age, sex, race/ethnicity, and income. Findings suggested ACEs were inversely related to mindfulness (B = −0.04, SE = 0.01; 95% CI = −0.07, −0.01; p < 0.05), mindfulness was inversely related to disordered eating (B = −1.27, SE = 0.23; 95% CI = −1.74, −0.80; p < 0.0001), and ACEs were positively related to disordered eating before (B = 0.17, SE = 0.04; 95% CI = 0.09, 0.26; p = 0.0001) and after (B = 0.13, SE = 0.04; 95% CI = 0.05, 0.21; p = 0.002) adjusting for mindfulness. Mediation analysis results indicated that the link between ACEs and disordered eating was significantly mediated by mindfulness (B = 0.05, SE = 0.02; 95% CI = 0.01, 0.09; p < 0.05). Evidence produced in this study confirmed existing findings concerning the positive association between ACEs and disordered eating among young adults, and these outcomes helped fill a knowledge gap regarding whether mindfulness mediates the link between ACEs and disordered eating. Future intervention studies should identify health-enhancing mindfulness approaches and then test whether the adoption of mindfulness practices can alleviate and prevent disordered eating among young adults with high ACEs.